Kepatuhan Hukum Pengendara Sepeda Motor Menyalakan Lampu Utama pada Siang Hari di Kabupaten Halmahera Selatan - Syafari, Tri; Robo, Basto Daeng (Faculty of Law, Khairun University, 2019)
Motorcycle riders in southern Halmahera Regency have not complied and obeyed the provisions of Article 293 paragraph (2) of the LLAJ Law concerning the obligation of motorcycle riders to turn on their lights during the day. This happened because in facing the disobedience of the driver, the South Halmahera Sat Lantas Police had not taken repressive measures such as giving a TOSS statement but the action taken was still limited to preventive action. The preventive measure is to disseminate information about the obligation to turn on lights during the day by motorcyclists. In addition, community ignorance and the low level of community discipline. Then the weak sanctions imposed by law enforcement.